PWE-211 Evaluation of clinical and radiological features that predict malignant transformation in small cystic lesions of the pancreas. (22nd June 2015) - Keane, MG; Dadds, HR; El Sayed, G; Luong, T; Fusai, GK; Davidson, BR; Thorburn, D; Pereira, SP
Abstract : Introduction: Cystic lesions of the pancreas (CLP) are being detected with increasing frequency. Current methods of stratifying risk of malignant transformation are imperfect. The aim of this study was therefore to determine the incidence of high-risk lesions and define clinical and radiological features that predict malignancy in a large cohort of patients with CLP managed by surgery or surveillance. Method: A retrospective cohort study from January 2000 to December 2013 of patients over 18 years of age with a confirmed CLP evaluated in a tertiary referral hepatobiliary centre. Results: Of the 1, 090 patients diagnosed with a CLP during the study period, 768 patients were included in the study. A total of 141 patients were referred for immediate pancreatic resection, 570 entered surveillance while 57 had a malignant CLP which was unresectable at diagnosis (N=47) or were unfit for surgery (N=10). In those who underwent immediate resection, malignancy was present in 38% (54/141). During follow-up 2% (10/570) of those entering a surveillance programme underwent malignant transformation, although most instances were after discharge from active surveillance. Only two patients in the surveillance cohort underwent surgery, of which only one case was curative. Clinical and radiological features associated with a high-risk CLP included older age, associated symptoms, presence of a solid component or a dilated main pancreatic duct. Larger size did not correlate consistently with malignant transformation, particularly in IPMNs where the median size of benign lesions was larger than malignant IPMNs (30mm (range: 11–130) vs. 23mm (range: 15–56)). Conclusion: The sensitivity of diagnostic tests leading to immediate surgery for high risk CLP (malignant or mucinous CLP) was 92%, with a specificity of just 5%. Surveillance of CLP without high-risk features was associated with a low incidence of cancer development. This study supports the stratification of CLP based on worrisome clinical and radiological features. Disclosure of interest: None Declared.